Design and Fabrication of Casuarina Harvesting Machine*. (2018) - Krishnaraj, S.; Deshik Sandeep, S.; Poovarasan, R.; Magesh, D.; Ajay Sooria, K.V.; Kiran, R.
Abstract: Agrotech – a developing field which is essential for agriculture. Casuarina Equisetifolia is a widely grown species used for the production of paper and firewood. Casuarina grows up to 12 feet in height in a span of 3 to 4 years. They are rigid and hard. This makes harvesting of Casuarina difficult. It consumes more time, money and manpower. Our harvesting machine reduces all of these. Our machine is equipped with two chainsaw blades at the front sides which are run by a 2 HP motor. It provides high rpm for effective cutting of trees. The dual blade enables cutting of two trees at same time. It is equipped with a front shield for protecting the driver. Overall an acre of Casuarina can be harvested in a few hours thus saving time, money and manpower. Our machine can also be used to harvest crops like sugarcane and bamboo by adjusting the position of the blades by simple alteration mechanism in order to produce a low cost harvesting machine for the farmers.